TRANSLATING METAPHORES FROM ENGLISH INTO INDONESIAN: PROBLEMS AND SOLUTIONS - Hartono, Rudi (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Translating metaphors is unique and specific. It needs an extraordinary skill and knowledge because it is different from translating ordinary texts. Translators of metaphors should pay attention to not only the meaning but also the context and culture of both source text and target text. Translating a metaphor is not just transferring the meaning but replacing the metaphor itself into the target language culturally and contextually accepted. It is suggested that translator can use semantic translation method when he or she translates metaphors, reproduces the same metaphors, replaces metaphors with metaphors or translate metaphors by similes. Keywords: translation, metaphor, tenor, vehicle, semantic translation method